2002
DOI: 10.1063/1.1452657
|View full text |Cite
|
Sign up to set email alerts
|

High saturation magnetization films of FeCoCr

Abstract: Thin (∼1000 Å) films of (Fe54Co46)1−xCrx have been prepared by magnetron sputtering on Si/SiO2 substrates. The films were shown to be body-centered-cubic and (110) textured. It was found that the Fe54Co46 films possess a saturation magnetization of 24.5 kG at room temperature. Doping the Fe54Co46 films with Cr in the range of 0–13 at. % increased corrosion resistance, electrical resistivity, and reduced the saturation magnetization as a function of the amount of added Cr. The coercivity of both doped and undop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…15 Easy and hard axis hysteresis loops for each film were determined using an SHB model 109 hysteresis loop tracer operating at 50 Hz. In all cases the composition of the magnetic layers was Co 35 Fe 65 ͑written hereafter as CoFe͒.…”
Section: Methodsmentioning
confidence: 99%
“…15 Easy and hard axis hysteresis loops for each film were determined using an SHB model 109 hysteresis loop tracer operating at 50 Hz. In all cases the composition of the magnetic layers was Co 35 Fe 65 ͑written hereafter as CoFe͒.…”
Section: Methodsmentioning
confidence: 99%
“…1͑a͔͒. [2][3][4] The saturation magnetostriction is also very large 1 with values of the constant s from 45-65ϫ10 Ϫ6 which in polycrystalline films if stresses are large, can result in large nonuniform local magnetostrictive anisotropies and potentially high H c . However, Platt et al 3 reported that a significant reduction in H c from 140 to 12 Oe was observed when Fe 50 Co 50 was grown on CoO.…”
Section: Introductionmentioning
confidence: 99%
“…If the main pole is magnetised to saturation along the zaxis, the stray field at the surface of the pole will be equal to 2pM s , where M s is the saturation magnetisation. The highest M s materials, such as FeCoCr [3], have M s of 1950 emu=cm 3 , giving a maximum vertical field of around 12 kOe.…”
Section: The Write Headmentioning
confidence: 99%
“…The main pole dimensions at the ABS were 45 nm  75 nm. The pole M s was 1910 emu=cm 3 and the SUL M s was 955 emu=cm 3 . The spacing between the ABS and the SUL was 25.5 nm, with a 13 nm thick recording layer extending from 7.5 to 20.5 nm from the ABS and a 5 nm seed layer between the recording layer and the SUL.…”
Section: The Write Headmentioning
confidence: 99%